A12 HDAC4 interacts with huntington and HDAC4 reduction decreases cytoplamsic aggregation and rescues synaptic dysfunction in HD mouse models. (29th August 2012) - Mielcarek, M; Landles, C; Weiss, A; Bradaia, A; Seredenina, T; Inuabasi, L; Wadel, K; Touller, C; Butler, R; Robertson, J; Franklin, SA; Smith, DL; et al.
Abstract : Histone deacetylase (HDAC) 4 is a transcriptional repressor that contains a glutamine rich domain. We have found that HDAC4 associates with mutant exon-1 and full length HTT in vivo in a polyQ length-dependent manner and co-localises predominantly with cytoplasmic inclusions in the brains of HD mouse models. HDAC4 knock-down inhibited aggregate formation in both the R6/2 (N-terminal fragment) and HdhQ150 (full length knock-in) mouse models of HD. This reduction in aggregation occurred in the cytoplasm, consistent with the subcellular localisation of HDAC4 in mouse brain, and was associated with a restoration of synaptic function. There was no evidence for HDAC4 translocation to the nucleus during disease progression, HDAC4 knock-down had no effect on HTT aggregation in the nucleus and no impact on global transcriptional dysregulation. Knock-down of HDAC4 improved motor co-ordination, as determined by rotarod performance, neurological phenotypes and extended survival. This provides a clear demonstration that cytoplasmic pathogenic mechanisms contribute to HD-related neurodegenerative phenotypes and identifies HDAC4 as a therapeutic target for HD. Our demonstration that the administration of SAHA decreases HDAC4 protein but not Hdac4 mRNA in vivo indicates that HDAC4 provides a mechanism of targeting mutant HTT that is amenable to small molecule therapeutics.